On the textual basis of Old Prussian Enchiridion used by Mažiulis (1966) - Dini, Pietro U. (Baltistica, 2020)
In his Prūsų kalbos paminklai (1966) V. Mažiulis knew two copies of the OPr Enchiridion which at that time were in Tübingen („T-Exemplar“) and in Dresden („D-Exemplar“). In the paper, relying on the newly discovered materials, I think to have established that the copy Mažiulis labeled „T-Exemplar“ corresponds to the „B1-Exemplar“ now at the Staatsbibliothek zu Berlin-Preußischer Kulturbesitz (Berlin, Unter den Linden; placement: Lib. impr. rar. Quart. 182). Some other aspects related to Mažiulis’ edition are also commented on.